Analysis of Factors Influencing the Shift in Transportation Mode from Private Vehicle and Public Transportation Users to Mass Rapid Transit (MRT) Routes in Surabaya - Adinda Ayumas Putri Kusuma Dewi; Wahju Herijanto (G-Tech: Jurnal Teknologi Terapan, 2026)
Proper planning in creating a policy is the first step needed in addressing urban transportation problems. Therefore, the Surabaya government together with Mott MacDonald and Pricewaterhouse Coopers (PwC) conducted a feasibility study to provide structured mass transportation in accordance with the target of Sustainable Development Goals (SDGs) in point 11, namely providing access to a safe, affordable, accessible and sustainable transportation system for all by increasing public transportation, considering that Surabaya is one of the priorities of the Sustainable Urban Mobility Plan (SUMP) study in the Gerbangkertosusila area prepared by the East Java Provincial Government. This study aims to determine what factors influence the shift in MRT transportation modes. The method used is logistic regression with a survey using the Stated Preference method with tariff and frequency change scenarios. The research subjects were users of private vehicles and public transportation that pass through the MRT plan route. Based on the results of the logistic regression analysis which set a p value 0.05, the attributes that influence the shift in transportation modes by private vehicles are income/pocket money with a p value <0.01, travel time from the point of origin to the destination with a p value <0.01, transportation costs with a p value of 0.014, special parking fees <0.01 and the mode of transportation used with a p value <0.01. Meanwhile, for public transportation, these attributes are ownership of a driving license with a p value of 0.017, waiting time at the bus stop with a p value <0.01, travel time from the origin to the destination with a p value <0.01 and ownership of a private vehicle with a p value <0.01Proper planning in creating a policy is the first step needed in addressing urban transportation problems. Therefore, the Surabaya government together with Mott MacDonald and Pricewaterhouse Coopers (PwC) conducted a feasibility study to provide structured mass transportation in accordance with the target of Sustainable Development Goals (SDGs) in point 11, namely providing access to a safe, affordable, accessible and sustainable transportation system for all by increasing public transportation, considering that Surabaya is one of the priorities of the Sustainable Urban Mobility Plan (SUMP) study in the Gerbangkertosusila area prepared by the East Java Provincial Government. This study aims to determine what factors influence the shift in MRT transportation modes. The method used is logistic regression with a survey using the Stated Preference method with tariff and frequency change scenarios. The research subjects were users of private vehicles and public transportation that pass through the MRT plan route. Based on the results of the logistic regression analysis which set a p value 0.05, the attributes that influence the shift in transportation modes by private vehicles are income/pocket money with a p value <0.01, travel time from the point of origin to the destination with a p value <0.01, transportation costs with a p value of 0.014, special parking fees <0.01 and the mode of transportation used with a p value <0.01. Meanwhile, for public transportation, these attributes are ownership of a driving license with a p value of 0.017, waiting time at the bus stop with a p value <0.01, travel time from the origin to the destination with a p value <0.01 and ownership of a private vehicle with a p value <0.01.